Identification of an effective fraction from Ampelopsis Radix with anti-dengue virus activities in vitro and in vivo. (12th June 2023) - Tian, Chunyang; Huang, Hefei; zheng, Yuanru; He, Xuemei; Yan, Lijun; Shi, Lingzhu; Yang, Tangjia; Chen, Xi; Yang, Jiabin; Lu, Zibin; Cao, Huihui; Zhao, Wei; et al.
Abstract: Ethnopharmacological relevance: Dengue virus (DENV) infection is a global public health issue without effective therapeutic interventions. Chinese medicine with heat-clearing and detoxifying properties has been frequently used in the treatment of viral infection. Ampelopsis Radix (AR) is a traditional Chinese medicine for clearing heat and detoxification that has been widely used in the prevention and treatment of infectious diseases. However, no studies on the effects of AR against viral infection have been reported, thus far. Aim of the study: To explore the anti-DENV activities of the fraction (AR-1) obtained from AR both in vitro and in vivo . Materials and methods: The chemical composition of AR-1 was identified by liquid chromatography-tandem MS (LC‒MS/MS). The antiviral activities of AR-1 were studied in baby hamster kidney fibroblast BHK-21 cells, ICR suckling mice and induction of interferon α/β (IFN-α/β) and IFN-γ R −/− (AG129) mice. Results: Based on LC‒MS/MS analysis, 60 compounds (including flavonoids, phenols, anthraquinones, alkaloids and other types) were tentatively characterized from AR-1. AR-1 inhibited the cytopathic effect, the production of progeny virus and the synthesis of viral RNA and proteins by blocking DENV-2 binding to BHK-21 cells. Moreover, AR-1 significantly attenuated weight loss, decreased clinical scores and prolonged the survival of DENV-infected ICR suckling mice. Critically, the viral load in blood, brain and kidney tissues and the pathological changes in brain were remarkably alleviated after AR-1 treatment. Further study on AG129 mice showed that AR-1 obviously improved the clinical manifestations and survival rate, reduced viremia, attenuated gastric distension and relieved the pathological lesions caused by DENV. Conclusions: In summary, this is the first report that AR-1 exhibits anti-DENV effects both in vitro and in vivo, which suggests that AR-1 may be developed as a therapeutic candidate against DENV infection. Graphical abstract: Image 1 Highlights: AR-1 from Ampelopsis Radix was identified as a novel antiviral candidate towards DENV. The anti-DENV effect of AR-1 was initiated at the stage of virus adsorption to the cell surface. AR-1 can be used against DENV not only in vitro, but also in vivo for the treatment of dengue.